'Ménage à trois': a selfish genetic element uses a virus to propagate within Thermotogales. (2nd March 2015) - Lossouarn, Julien; Nesbø, Camilla L.; Mercier, Coraline; Zhaxybayeva, Olga; Johnson, Milo S.; Charchuck, Rhianna; Farasin, Julien; Bienvenu, Nadège; Baudoux, Anne‐Claire; Michoud, Grégoire; Jebbar, Mohamed; Geslin, Claire
Summary Prokaryotic viruses play a major role in the microbial ecology and evolution. However, the virosphere associated with deep‐sea hydrothermal ecosystems remains largely unexplored. Numerous instances of lateral gene transfer have contributed to the complex and incongruent evolutionary history of Thermotogales, an order well represented in deep‐sea hydrothermal vents. The presence of clustered regularly interspaced short palindromic repeats (CRISPR) loci has been reported in all Thermotogales genomes, suggesting that these bacteria have been exposed to viral infections that could have mediated gene exchange. In this study, we isolated and characterized the first virus infecting bacteria from the order Thermotogales, Marinitoga piezophila virus 1 (MPV1). The host, Marinitoga piezophila is a thermophilic, anaerobic and piezophilic bacterium isolated from a deep‐sea hydrothermal chimney. MPV1 is a temperate Siphoviridae‐like virus with a 43.7 kb genome. Surprisingly, we found that MPV1 virions carry not only the viral DNA but preferentially package a plasmid of 13.3 kb (pMP1) also carried by M. piezophila. This 'ménage à trois' highlights potential relevance of selfish genetic elements in facilitating lateral gene transfer in the deep‐sea biosphere.